2023
DOI: 10.1098/rsos.230860
|View full text |Cite
|
Sign up to set email alerts
|

takeout gene expression is associated with temporal kin recognition

Ahva L. Potticary,
Elizabeth C. McKinney,
Patricia J. Moore
et al.

Abstract: A key component of parental care is avoiding killing and eating one's own offspring. Many organisms commit infanticide but switch to parental care when their own offspring are expected, known as temporal kin recognition. It is unclear why such types of indirect kin recognition are so common across taxa. One possibility is that temporal kin recognition may evolve through alteration of simple mechanisms, such as co-opting mechanisms that influence the regulation of timing and feeding in other contexts. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…After we observed that the focal females’ larvae had hatched, we provided the focal female with an unrelated, mixed brood of 10 larvae. Burying beetles identify their offspring temporally and eat any larvae that arrive too early on the carcass (Oldekop et al, 2007, Potticary et al, 2023); thus, we only provided females with larvae after her own larvae had hatched. For the full care treatment, we allowed females to associate with larvae until at least two of the larvae had dispersed from the breeding carcass (∼7-8 days).…”
Section: Methodsmentioning
confidence: 99%
“…After we observed that the focal females’ larvae had hatched, we provided the focal female with an unrelated, mixed brood of 10 larvae. Burying beetles identify their offspring temporally and eat any larvae that arrive too early on the carcass (Oldekop et al, 2007, Potticary et al, 2023); thus, we only provided females with larvae after her own larvae had hatched. For the full care treatment, we allowed females to associate with larvae until at least two of the larvae had dispersed from the breeding carcass (∼7-8 days).…”
Section: Methodsmentioning
confidence: 99%